2013
DOI: 10.1097/nmd.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Life and Death and Suicidality Among Inpatient Female Adolescents With Eating Disorders

Abstract: This study investigated whether attitudes about life and death are associated with suicidal behavior in eating disorders (EDs). We examined 43 nonsuicidal inpatients with EDs, 32 inpatients with EDs who attempted suicide, and 21 control participants with scales assessing attitudes to life and death, body-related attitudes, core ED symptoms, depression, and anxiety. Both ED groups showed less attraction to life and more repulsion from life than did the control participants. The suicide attempters showed greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
2
26
0
2
Order By: Relevance
“…EAT‐26 is a 26‐item self‐rating scale that assesses a person’s pursuit of thinness, dieting behavior, and control overeating . It serves as a key tool in the evaluation of DEBs in community populations, and has been shown to successfully differentiate among Israelis, those with and without EDs . An EAT‐26 score of ≥20 is considered pathological.…”
Section: Methodsmentioning
confidence: 99%
“…EAT‐26 is a 26‐item self‐rating scale that assesses a person’s pursuit of thinness, dieting behavior, and control overeating . It serves as a key tool in the evaluation of DEBs in community populations, and has been shown to successfully differentiate among Israelis, those with and without EDs . An EAT‐26 score of ≥20 is considered pathological.…”
Section: Methodsmentioning
confidence: 99%
“…The Y-BOCS and YBC-EDS have been previously used in ED patients (Crow, Agras, Halmi, Mitchell, & Kraemer, 2002;Pollice, Kaye, Greeno, & Weltzin, 1997), including in Israeli samples (Yackobovitch-Gavan et al, 2009). 2.2.2 | Self-rating scales 1. Maladaptive eating-related parameters were assessed using the 26-item Eating Attitude Test-26 (EAT-26; Garner, Bohr, & Garfinkel, 1982) that has been shown to successfully differentiate Israeli patients with EDs from non-ED controls (Stein et al, 2013). The internal consistency of the EAT-26 in the present study was α = 0.93 and α = 0.94 for the admission and discharge samples, respectively.…”
Section: Interviewsmentioning
confidence: 71%
“… Maladaptive eating‐related parameters were assessed using the 26‐item Eating Attitude Test—26 (EAT‐26; Garner, Bohr, & Garfinkel, ) that has been shown to successfully differentiate Israeli patients with EDs from non‐ED controls (Stein et al, ). The internal consistency of the EAT‐26 in the present study was α = 0.93 and α = 0.94 for the admission and discharge samples, respectively. Depression was assessed using the 21‐item Beck Depression Inventory (BDI; Beck, Ward, Mendelson, Mock, & Erbaugh, ) previously used in patients with EDs (Pollice et al, ), including in Israeli samples (Yackobovitch‐Gavan et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Suicide attempts in EDs have been found in 3–20% of patients with AN and in 25–30% of patients with BN . In a recent study of female adolescent inpatients with EDs comparing suicidal and nonsuicidal patients, it was found that suicide attempters had significantly more negative attitudes toward their bodies compared to nonattempters …”
Section: Introductionmentioning
confidence: 99%
“…10 In a recent study of female adolescent inpatients with EDs comparing suicidal and nonsuicidal patients, it was found that suicide attempters had significantly more negative attitudes toward their bodies compared to nonattempters. 11 One of the most commonly used tools to assess pediatric depressive symptoms is the Children's Depression Inventory (CDI), 12 which was developed as an age-appropriate revision of the Beck Depression Inventory. 13 Designed as a screening rather than a diagnostic tool, 14 the CDI has construct and discriminative validity in clinical and community samples.…”
Section: Introductionmentioning
confidence: 99%